The Madness of Cati’s Madman (Miscelânea: Journal of Literature and Social Life, 2024)
This paper discusses O louco do Cati [The madman of Cati] by Dyonelio Machado, from a perspective that seeks to articulate the relationships between literature and madness. Thus, we propose that the madness of the title character of this Dyonelian novel is mythical, historical and political, fictionalized in the midst of childhood trauma and police persecution. What ironically reveals itself in the narrative, finally, is that the madman and the madness – fictional or real – are an unfathomable amalgam of myth and mystery.
Keywords: Madness